A roda girou o Tambu repicou e o Candongueiro ensinou: o Turi Vimba quilombo Cafundó (Salto de Pirapora-SP) tecendo linhas de vida. - Lima, Laíne Horta (Universidade Federal de São Carlos, 2020)
This study aims to reflect on questions about the narratives, knowledge and resistance of the quilombolas of Cafundó (Salto de Pirapora - SP) that show, with power, other ways of living the world, creating possibilities through the creative process experienced and reaffirmed by young quilombolas, giving a new meaning to the Jongo wheel, rescuing the Cuppia language existing in the quilombo and thus producing counter-hegemonic narratives. The narratives produced by colonialism propagate the false idea of subordinate when referring to the black people. Violently silences centuries of knowledge production significantly elaborated by the black African and diaspora population. By highlighting the narratives of the Cafundó quilombolas in relation to the resignification of Jongo in their territory, it confronts the hegemonic knowledge of colonialism while allowing us to understand the tricks poetically elaborated by the quilombolas of Cafundó when resisting and retelling their own history. The study is based on orality and is influenced by the studies of Oral History (PORTELLI, 2010) and Oral Tradition (HAMPATÊ, 1982).
The wheel spined Tambu repicou and the Candongueiro teached: Turi Vimba quilombo Cafundó (Salto de Pirapora-SP) weaving life lines.
Keywords: Cafundó; Jongo; Quilombo; Education for ethnic racial relations; Educação para as relações étnico raciais; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO